Intercropping of soybean and proso millet for biomass production - Milenković Milena; Simić Milena; Brankov Milan; Milojković-Opsenica Dušanka; Kresović Branka; Dragičević Vesna (Journal on Processing and Energy in Agriculture, 2019)
Sustainable agriculture considers production of high quality food and feed with minimal impact on environment. Intercropping is one of the most efficient ways to produce valuable biomass for animal feed rich in nutrients. Intercrop combinations: alternating rows of soybean and proso millet (S-M), alternating strips with 2 rows of soybean and 2 rows of millet (SS-MM-SS) and alternating strips with 2 rows of soybean and 4 rows of millet (SS-MMMM-SS); single crop of soybean and single crop of proso millet were tested. The effect of bio-fertilizer Coveron was also followed. Aboveground biomass was harvested and land equivalent ratio (LER), as well as leaf area index (LAI) was determined. All intercropping combinations increased LAI of soybean when compared to monocrop, to 43% and 84% in SS-MM-SS combination with and without Coveron, respectively. Coveron slightly increased LAI. The highest values of biomass yield were obtained in S-M intercrop for soybean (39% and 42% higher in relation to monocrop, in combination with and without Coveron, respectively) and in monocrop for proso millet. Nevertheless, the highest LER value was obtained for SS-MM-SS combination without Coveron (1.12). In intercrops treated with Coveron slightly lower LER values were obtained for S-M and SS-MMMM-SS combination (0.97 and 0.98, respectively). Irrespective to sowing way, results indicate that 1:1 ratio of soybean and proso millet in intercrop (S-M and SS-MM-SS combinations) is the most promising way to achieve high biomass yield.